Abu Abdullah Ibn Musa Al-Khawarizmi (Pelopor Matematika dalam Islam) - Fathurrahman Muhtar (Universitas Islam Negeri (UIN) Mataram, 2014)
Under the Caliph al-Ma’mũn (reigned 813-833) Al-Khwārizmī became a member of the “House of Wisdom” (Dār Al-Hikma), a kind of academy of scientists set up at Baghdad, probably by Caliph Harũn Al-Rashīd, but owing its preeminence to the interest of Al-Ma’mũn, a great patron of learning and scientific investigation. It was for Al-Ma’ũn that Al-Khwārizmī composed his astronomical treatise, and his Algebra also is dedicated to that ruler. Using the old Roman numeral system made advanced math next to impossible. With a number system that goes from 0 to 9, Al-Khawarizmi is able to develop fields such as algebra, which he initially used to calculate Muslim inheritance laws. He builds more on the geometry of the Greeks, and develops the basic ideas many high school math students can recognize today. But his real issue remains with the number zero. It cannot be proven to exist using math. The old Indian texts insist zero divided by zero equals zero. But Al-Khawarizmi knows that any division by zero is impossible. Eventually he comes to the conclusion that the zero must simply be accepted without being proven. Furthermore, he reports to the Caliph Al-Ma'mun that belief in Allah is the same: it cannot be proven using science, but must be accepted on faith in the religion. Al-Khawarizmi was as much a philosopher as he was a mathematician. In addition to math, he writes a compendium on geography that lists the latitude and longitude of 2,400 cities around the world. He also writes books on the astrolabe, sundials, and even the Jewish calendar. For 700 years after his death, European mathematicians cite him in their works, referring to him as “Algorismi”. The modern word for a complex mathematical formula, algorithm, is derived from his name. His legacy lives on, even if the modern world that he helped build has all but forgotten of his contributions.